Application of the numbered heads together learning model to improve learning outcomes of Christian religion education - Deflita R. N Lumi; Thofan Rame (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The low learning outcomes of Christian Religious Education in class IV students at SDK Scriptura Bengel Talaud Islands Regency compared to other subjects. To improve learning achievement in Christian Religious Education, it is necessary to have innovative learning models that can motivate students to be active in learning. The Numbered Heads Together Learning Model is the implementation of a learning process in which the teacher divides students into several heterogeneous groups and gives numbering to each group member to work on each given problem. So that the application of the Numbered Heads Together Learning Model can improve the learning outcomes of Christian Religious Education in class IV SDK Scriptura Bengel, Talaud Islands Regency. The research was conducted on fourth-grade students at SDK Scriptura Bengel consisting of 7 girls and 4 boys with a total of 11 people. This research was conducted from April to May 2022. The method uses a class action research design with the stages of Planning, Action Implementation, Observation, and Reflection. The data were analyzed using the completeness technique of learning outcomes with the formulaKB=T/T1 x 100%. The results showed that the application of the Numbered Heads Together Learning model could improve the learning outcomes of Christian Religious Education from cycle I to cycle II with the subject